Ecological aspects and genetic diversity of Shorea balangeran in two forest types of Muara Kendawangan Nature Reserve, West Kalimantan, Indonesia - FITRI INDRIANI; ULFAH J SIREGAR; DEDEN D MATRA; ISKANDAR Z SIREGAR (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Indriani F, Siregar U, Matra DD, Siregar IZ. 2019. Ecological aspects and genetic diversity of Shorea balangeran in two forest types of Muara Kendawang Nature Reserve, West Kalimantan, Indonesia. Biodiversitas 20: 482-488. Shorea balangeran (balangeran) belongs to the Dipterocarpaceae family that is distributed naturally in Indonesia with a wide range of ecological conditions including peat swamp and heath forests. Good adaptability of S. balangeran remains unknown concerning molecular (genetic) responses that are important to provide scientific knowledge for supporting forest restoration, especially for peatland restoration efforts. The main objective of this research was to analyze the ecological aspects and genetic diversity of S. balangeran in two types of forests, namely: peat forests (wetland) and heath forests (dry land). Field research was conducted in Muara Kendawangan Nature Reserve, West Kalimantan following standard vegetation analysis by establishing purposively sample plots (50 m x 50 m). Genetic diversity was assessed by RAPD analysis using ten random polymorphic primers. Results showed that both in heath and peat forests, S. balangeran was dominant, but only at pole and tree stages indicating that poor regeneration capacity of S. balangeran. This finding also confirmed the critically endangered status of S. balangeran as listed in the IUCN Red List of Threatened Species. Genetic analysis using RAPD did not show a clustering of S. balangeran between peat forest and heath forest populations, indicating that S. balangeran has good adaptability to grow in both forest types.